Generalized eruptive histiocytoma in a 12-year-old boy. - Can, B.; Zindancı, I.; Kavala, M.; Kocaturk, E.; Turkoglu, Z.; Koç, M.; Zemheri, E. (European Journal of Pediatric Dermatology, 2011)
Generalized eruptive histiocytoma is a rare, benign, papular, self-healing histiocytosis characterized by recurrent crops of small, firm, tan to reddish papules that appear in a symmetrical fashion on the face, trunk and arms. They resolve over months with residual hyperpigmented macules. Although generally regarded as a disorder of adults, generalized eruptive histiocytoma has been seen in childhood. Here is reported a case of generalized eruptive histiocytoma in a 12-year-old male.